2011
DOI: 10.1108/14668201111178175
|View full text |Cite
|
Sign up to set email alerts
|

Training, knowledge and confidence in safeguarding adults: results from a postal survey of the health and social care sector in a single county

Abstract: PurposeThe purpose of this paper is to clarify the relationship between safeguarding adults training, staff knowledge and confidence.Design/methodology/approachA total of 647 responses from a cross sectional postal sample survey of the health and social care sector in Cornwall, were analysed.FindingsDifferences in knowledge and confidence around safeguarding were observed between staff groups and agencies. Training contributed to an approximately 20 per cent increase in knowledge and a ceiling effect was noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Put another way, a linear model of change can be blown off course by insufficient resources, role confusion and professional values; imposed change can lead to perfunctory performance, whilst practitioners may feel unable to respond positively to recommendations when they feel excluded from dialogue about change and when recommended forms of practice feel disconnected from the dilemmas they encounter (Preston-Shoot, 2001). Equally, agencies may not be culturally and organisationally aligned to implement the findings and recommendations, and it will take more than training to promote collaboration, challenge professional stereotypes and ensure that the practice environment enables the use of evidence from research and reviews (Pike et al, 2011;Pike and Wilkinson, 2013). Considerable faith has been placed in training and in procedures but within an unchanged single and multi-agency context.…”
mentioning
confidence: 99%
“…Put another way, a linear model of change can be blown off course by insufficient resources, role confusion and professional values; imposed change can lead to perfunctory performance, whilst practitioners may feel unable to respond positively to recommendations when they feel excluded from dialogue about change and when recommended forms of practice feel disconnected from the dilemmas they encounter (Preston-Shoot, 2001). Equally, agencies may not be culturally and organisationally aligned to implement the findings and recommendations, and it will take more than training to promote collaboration, challenge professional stereotypes and ensure that the practice environment enables the use of evidence from research and reviews (Pike et al, 2011;Pike and Wilkinson, 2013). Considerable faith has been placed in training and in procedures but within an unchanged single and multi-agency context.…”
mentioning
confidence: 99%
“…They concluded that staff knowledge was below expectations and that “(c)arefully designed verification of the impact” of training was required. Another study (Pike et al , 2011) concluded that training improved participants’ knowledge by 20 per cent. Without sustained use subsequently, knowledge and skills acquired through training will decay.…”
Section: Finding Evidencementioning
confidence: 99%
“…Additionally, research into social work practices has established that organisational intentions expressed through training and policies are not always reflected in the practices of individual staff at a micro-level (Healy and Wint, 1998;Hughes and Wearing, 2007). Though there is some acknowledgement of the need to ensure that training is transferred into practice when designing training programmes, and that this knowledge transfer requires a receptive organisational culture to be effective (Pike et al, 2010(Pike et al, , 2011, little consideration is given to the significance of the value frameworks of individual members of staff and how they may deleteriously influence their behaviour when caring for people after they have left the "classroom", particularly when working beyond the scrutiny of their peers and managers (Moore, 2017a).…”
Section: So What Of Commissioning?mentioning
confidence: 99%